Microbial contamination and antimicrobial resistance in dried fish from informal markets in Gauteng Province, South Africa: A One Health food safety assessment - Siphiwe Rendy Nkosi; Mpinda Edoaurd Tshipamba; Ngoma Lubanza; B.G. Mokolopi; Mulunda Mwanza (Veterinary World, 2026)
Background and Aim: Dried fish sold in informal markets is an affordable source of protein but may be vulnerable to microbial contamination because of inadequate hygiene and handling practices. This study aimed to assess microbial contamination levels, identify bacterial isolates using 16S rRNA sequencing, and determine the antimicrobial resistance (AMR) profiles of bacteria recovered from sun-dried, smoked, and salted fish sold in informal markets in Gauteng Province, South Africa. The research addressed limited information on the microbiological quality and AMR of dried fish sold in South African informal markets, particularly the integration of culture-based, molecular, and resistance-profiling approaches in a One Health framework. Materials and Methods: A total of 140 dried fish samples (80 sun-dried, 40 smoked, and 20 salted) were collected from 12 informal markets in Johannesburg and Pretoria using convenience sampling. Total bacterial counts (TBC) were determined on nutrient agar, followed by phenotypic characterization and molecular identification using 16S rRNA gene sequencing. Antimicrobial susceptibility testing was performed using the disk diffusion method against seven antibiotics. Data were analyzed using descriptive statistics, analysis of variance with Bonferroni correction, and chi-square tests, with statistical significance set at p < 0.05. Results: TBC ranged from 0.8 × 10⁷ to 5.34 × 10⁷ colony forming units/g, with a significant difference between sun-dried and salted fish after Bonferroni adjustment (p = 0.012). Sixty-seven bacterial isolates were identified, dominated by Clostridium spp. (10/67, 14.92%), Staphylococcus spp. (8/67, 11.94%), Staphylococcus xylosus (6/67, 8.95%), and Klebsiella pneumoniae (5/67, 7.46%), including Clostridium botulinum (2/67, 2.98%). High resistance was observed to streptomycin (73.1%) and erythromycin (58.2%), and several bacterial isolates exhibited multidrug resistance. No significant differences in bacterial counts were detected among sampling locations (p = 0.457). Conclusion: This study provides critical evidence of multidrug-resistant bacteria, including C. botulinum, in dried fish from informal markets, highlighting serious food safety and public health risks. Findings underscore the need for enhanced hygiene practices, vendor training, and regulatory oversight to mitigate contamination and the spread of AMR in informal food systems. Keywords: antimicrobial resistance, dried fish, food safety, informal markets, microbial contamination, One Health, public health, South Africa.